Solar x-ray control of the ionospheric absorption measured by the sweep frequency method - Gupta G.P. (My University, 2025)
The ionospheric absorption data measured by the sweep frequency method have been compared with the solar x-ray data in the band of 1-8 Å during quiet- and disturbed-sun conditions. The degree of solar x-ray control of the ionospheric absorption and the corresponding limit of solar x-ray flux have been discussed. © 1978 Indian Academy of Sciences.